2022
DOI: 10.2991/aebmr.k.220204.035
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of President Grants for Micro Business Productive (BPUM) to Increase Productivity of MSMEs Amid Adaptation of New Normal: A Research Proposal

Abstract: This study aims to analyze the research on presidential assistance in increasing the productivity of MSMEs and analyze the effect of the beneficiaries of presidential aid assistance. This analysis uses a normative juridical approach using a literature study. Data collection was carried out qualitatively, describing it in words to become a sentence that can be understood, expanded, and accounted for. The deductive method, namely drawing conclusions or reasoning processes from general statements to reach certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
8

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…In contrast to MSMEs with lower levels of financial literacy, (Aulia et al, 2023;Maswin & Sudrajad, 2023;Priyana, 2022)found that MSMEs with higher levels of financial literacy typically achieve more profitability, sales growth, and business expansion. Similarly, (Klapper & Farber, 2016) emphasized the value of financial literacy in improving MSME owners' capacity to manage debt, obtain financing, and reduce financial risks-all of which eventually improve business outcomes.…”
Section: Literature Review 1 Financial Literacy and Msme Performancementioning
confidence: 99%
“…In contrast to MSMEs with lower levels of financial literacy, (Aulia et al, 2023;Maswin & Sudrajad, 2023;Priyana, 2022)found that MSMEs with higher levels of financial literacy typically achieve more profitability, sales growth, and business expansion. Similarly, (Klapper & Farber, 2016) emphasized the value of financial literacy in improving MSME owners' capacity to manage debt, obtain financing, and reduce financial risks-all of which eventually improve business outcomes.…”
Section: Literature Review 1 Financial Literacy and Msme Performancementioning
confidence: 99%
“…Usaha-usaha ini sangat penting untuk menciptakan lapangan kerja dan memperluas kesempatan kerja, berkontribusi secara signifikan terhadap pembangunan ekonomi negara (Marwanto et al, 2023). Akses ke sumber daya keuangan, dukungan teknis, dan bantuan pengembangan bisnis merupakan faktor kunci dalam memberdayakan UMKM untuk tumbuh, meningkatkan kapasitas produksi, dan menciptakan lapangan kerja baru (Amin et al, 2023;Priyana, 2022). Kebijakan pajak yang menguntungkan secara positif mempengaruhi keputusan investasi dan pertumbuhan bisnis UMKM, menyoroti pentingnya merancang kebijakan pajak yang memberikan insentif untuk pertumbuhan dan daya saing di sektor ini (Amelia et al, 2023).…”
Section: Pendahuluanunclassified
“…Pemerintah mengimplementasikan berbagai kebijakan dan program untuk mendukung pengembangan UMKM, termasuk reformasi regulasi, insentif fiskal, dan inisiatif pengembangan kapasitas (Dela Cruz et al, 2023;Priyana, 2022;Ramadhona et al, 2023). Intervensi ini bertujuan untuk mengatasi tantangan seperti keterbatasan akses keuangan, persaingan pasar, dan beban regulasi, serta memanfaatkan peluang seperti transformasi digital dan akses pasar baru (Rungani & Ward, 2023).…”
Section: Pendahuluanunclassified
“…UMKM di Kota Semarang menghadapi tantangan dalam mengakses perlindungan hukum, yang sangat penting untuk melindungi kepentingan mereka dan memastikan peluang pertumbuhan (Aresteria et al, 2023;Dwisvimiar, 2023). Kerangka hukum untuk hak milik, penegakan kontrak, dan penyelesaian sengketa tidak memadai, sehingga membuat UMKM rentan terhadap risiko seperti pencurian, penipuan, dan pelanggaran kontrak (Gunawan et al, 2023;Priyana, 2022). Kerentanan ini menghambat kemampuan mereka untuk bersaing secara efektif di pasar.…”
Section: Pendahuluanunclassified